2018
DOI: 10.17763/1943-5045-88.4.429
|View full text |Cite
|
Sign up to set email alerts
|

The Quandary of Youth Participatory Action Research in School Settings: A Framework for Reflecting on the Factors That Influence Purpose and Process

Abstract: Youth participatory action research (YPAR) is a form of critical participatory action research that provides young people with opportunities to identify injustices in their current social realities, to gather and analyze data about these phenomena, and to determine actions that will begin to rectify their negative outcomes. A growing body of evidence suggests that YPAR projects improve outcomes for individual youth as well as the organizations/settings they act on. Despite this, the extent to which YPAR can an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…That project utilized time both before and after school to engage youth researchers with research on the topic of antiracism and whiteness. These examples may reflect a tension with YPAR epistemology about youth researchers’ agency (Brion‐Meisels & Alter, ). Specifically, youth researchers may exercise their agency and opt not to participate in a project that they may otherwise be required to participate in during dedicated instructional time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That project utilized time both before and after school to engage youth researchers with research on the topic of antiracism and whiteness. These examples may reflect a tension with YPAR epistemology about youth researchers’ agency (Brion‐Meisels & Alter, ). Specifically, youth researchers may exercise their agency and opt not to participate in a project that they may otherwise be required to participate in during dedicated instructional time.…”
Section: Resultsmentioning
confidence: 99%
“…A recent theoretical case study suggested that implementation of YPAR in schoolbased settings may include a unique set of demands that need to be addressed by adult researchers (Brion-Meisels & Alter, 2018). Specifically, the authors described four tensions of YPAR in school-based settings: power sharing between stakeholders, time constraints, centralized control over policies, and increasing student agency within constrained educational settings (Brion-Meisels & Alter, 2018). Similarly, a study of one middle-school PAR project described challenges, essential processes, and considerations for implementation (Ozer et al, 2010).…”
Section: Implementation Of Ypar In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In schools, YPAR projects risk being schoolified, its aims of inquiry and action transformed into mere graded assignments (Rubin, Ayala, & Zaal, ). Brion‐Meisels and Alter () noted that the “context, relationship, and urgency within schools can make it difficult to center the critical, participatory, and transformational aspects of YPAR” (p. 447). As with these scholars, we search for ways to honor the liberatory aims of YPAR within institutional confines that often reproduce existing structural relationships, while also navigating the complex, sometimes fraught, politics of a school setting.…”
Section: Yparmentioning
confidence: 99%
“…YPAR therefore engages an epistemological and pedagogical commitment to center youth, which is unique in the education research landscape. However, YPAR scholars themselves frequently point out how difficult this work can be, especially within the structural constraints and increasing standardization of schools (Brion-Meisels & Alter, 2018;Buttimer, 2019;Rubin, Ayala, & Zaal, 2017). And while YPAR is a crucial approach for elevating the concerns and priorities of young people, it is not the only way that youth and adults can collaborate to produce knowledge.…”
mentioning
confidence: 99%